1918 Mont. Laws 6-7,9, ch. 2, §§ 1, 3, 8. - (:unkn) unknown (General Publisher, 1918)
Within thirty days from the passage and approval of this Act, every person within the State of Montana, who owns or has in his possession any fire arms or weapons shall make a full, true, and complete verified report upon the form hereinafter provided to the sheriff of the County in which such person lives, of all fire arms and weapons which are owned or possessed by him or her or are in his or her control, and on sale or transfer into the possession of any other person such person shall immediately forward to the sheriff of the County in which such person lives the name and address of that purchaser and person into whose possession or control such fire arm or weapon was delivered. § 3. Any person signing a fictitious name or address or giving any false information in such report shall be guilty of misdemeanor, and any person failing to file such report as in this Act provided, shall be guilty of a misdemeanor. § 8. For the purpose of this Act a fire arm or weapon shall be deemed to be any revolver, pistol, shot gun, rifle, dirk, dagger, or sword.
--
Keywords: REGISTRATION; DEFINITIONS